Avaliação Neurocognitiva de Doentes Esquizofrénicos Institucionalizados: da Dimensão Neurobiológica ao Viver Quotidiano - M. Alvarez (2005)
Introduction and Aims: Schizophrenia is a disease in which psychopathology, cognitive impairment and neurological minor signs (NMS) have a relevant role. These three factors, positively correlated, are conected to the patient's satisfactions. Acquiring quality of life (QL) is designed to be the ultimate objective in psychiatric rehabilitation. In a psychopathological point of view it is accepted that both positive and negative symptoms are correlated with QL. The cognitive impairment (eg. executive function) is as well, correlated with QL. In addition, there are some studies that demonstrate a relationship between these factors. In this way, the aim of this paper is to study the factors of QL that are more affected by cognitive impairment, psychopathology and NMS. Method: Observational cross-sectional study in 15 male schizophrenic patients. This evaluation method consists of: (1) cognition: administration of CFSCE - Conde Ferreira Standard Cognitive Evaluation (a neuropsychological battery of tests developed in CHCF); (2) NMS: administration of NES (Neurological Evaluation Scale); (3) Quality of Life: administration of QLS (Quality of Life Scale); (4) Psychopathology: administration of PANSS (Positive and Negative Syndrome Scale). Conclusions: We have found relevant correlations that allow us the following conclusions: QL areas most affected by the cognitive performance (verbal comprehension, perceptive organization, attention and concentration) are identified in an Occupational Level. In NMS we also found that the area of QL most affected is Social Network/ Social Activity satisfaction. The QL it is also affected by the presence of psychopathology modifications: the dimensions that have a major development are the Intrapsychic functions/ Interpersonal relations/Common Activities and Social Network/Social Activity, which correlate both with PANSS (total) and with positive and negative sub-scales. Finally, the Occupational/Time Occupation is associated with the total value and the psychopathology sub-scale of PANSS.